Caffeic Acid, a Polyphenolic Micronutrient Rescues Mice Brains against Aβ-Induced Neurodegeneration and Memory Impairment - Amjad Khan; Jun Sung Park; Min Hwa Kang; Hyeon Jin Lee; Jawad Ali; Muhammad Tahir; Kyonghwan Choe; Myeong Ok Kim (MDPI AG, 2023)
Oxidative stress plays an important role in cognitive dysfunctions and is seen in neurodegeneration and Alzheimer's disease (AD). It has been reported that the polyphenolic compound caffeic acid possesses strong neuroprotective and antioxidant effects. The current study was conducted to investigate the therapeutic potential of caffeic acid against amyloid beta (Aβ1-42)-induced oxidative stress and memory impairments. Aβ1-42 (5 μL/5 min/mouse) was administered intracerebroventricularly (ICV) into wild-type adult mice to induce AD-like pathological changes. Caffeic acid was administered orally at 50 mg/kg/day for two weeks to AD mice. Y-maze and Morris water maze (MWM) behavior tests were conducted to assess memory and cognitive abilities. Western blot and immunofluorescence analyses were used for the biochemical analyses. The behavioral results indicated that caffeic acid administration improved spatial learning, memory, and cognitive abilities in AD mice. Reactive oxygen species (ROS) and lipid peroxidation (LPO) assays were performed and showed that the levels of ROS and LPO were markedly reduced in the caffeic acid-treated mice, as compared to Aβ-induced AD mice brains. Moreover, the expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and heme oxygenase-1 (HO-1) were regulated with the administration of caffeic acid, compared to the Aβ-injected mice. Next, we checked the expression of ionized calcium-binding adaptor molecule 1 (Iba-1), glial fibrillary acidic proteins (GFAP), and other inflammatory markers in the experimental mice, which suggested enhanced expression of these markers in AD mice brains, and were reduced with caffeic acid treatment. Furthermore, caffeic acid enhanced synaptic markers in the AD mice model. Additionally, caffeic acid treatment also decreased Aβ and BACE-1 expression in the Aβ-induced AD mice model.